FINANCIAL LITERACY AS TECHNOLOGICAL ACCELERATION IN INVESTMENT DECISIONS FOR GENERATION Z IN INDONESIA - Pratama, Novi Solomasi; Purwanto, Purwanto (President University, 2024)
The purpose of this study is to examine the determinants of investment decisions with financial literacy as an mediating variable. By focusing on the aspects of technology ease, emotional intelligence, financial self-efficacy, and financial risk tolerance, this study determinants that guide investment decisions. In addition, financial literacy is integrated as an intervening variable to understand how financial understanding can mediate the relationship between the determinants and investment decisions. This approach provides a more in-depth and contextual insight into the dynamics of investment decision-making among the heterogeneous Generation Z. This study chose Jabodetabek, Indonesia as the focus location because this metropolitan area reflects the investment diversity of Generation Z who live in dynamic urban areas. Employing a quantitative approach, the study collected primary data through questionnaires from 118 individuals. Data analysis employed Structural Equation Modeling with Partial Least Squares (SEM-PLS), classical assumption tests, and hypothesis testing (F-test and T-test), alongside the determination of coefficients (R-square). The study found that emotional intelligence, financial literacy, and financial self-efficacy have a significant influence on investment decisions, while financial risk tolerance and technology ease have an insignificant influence. The study concludes that the influence of technology ease, emotional intelligence, financial self-efficacy, financial risk tolerance, and financial literacy can explain 66.90% of investment decisions.